Bitter rice - Chase, Graham; Holmes, Cecil ([S.l.] Film Australia, 1989)
An interview with Dante Buscayno by Film Australia when he was released from prison in 1986. How he organized the NPA in Tarlac and how he started a livelihood cooperative project among farmers, its advantages and disadvantages were some of the questions answered.
In English, Pilipino and Kapampangan.
Editor, Graham Chase ; Translations [by] Joy Balazo.
Keywords: Buscayno, Dante; Agricultural cooperative credit associations -- Philippines -- Tarlac; Agriculture, Cooperative -- Philippines -- Tarlac; Social work